Manajemen Strategis Lembaga Pendidikan Satu Atap: Studi Kasus Di Pondok Pesantren Anwarul Haromain Baruharjo Trenggalek - Madayani, Nany Soengkono; Mufidati, Khusnul; Fasya, Istiqlal Widyatama Ihsan; Mukaromah, Dewi (Universitas Islam Tribakti Lirboyo Kediri, 2025)
Islamic boarding schools are educational institutions that provide both formal and non-formal learning for their students. Anwarul Haromain Islamic Boarding School in Baruharjo, Durenan, Trenggalek, represents a modern Islamic education model that applies a mono-management system, integrating three formal education levels (junior high school, senior high school, and vocational school) under one institutional leadership. This research aims to analyze the implementation strategy, management process, and leadership pattern in developing a one-roof educational institution. The study employs a qualitative descriptive method with data collected through observation, interviews, and documentation. The findings reveal that leadership at Anwarul Haromain Islamic Boarding School is centered on the kiai as the visionary leader, supported by the heads of madrasah and administrative staff who act as policy executors. The mono-management system enhances effectiveness, efficiency, and institutional coordination, while challenges related to communication and resistance are mitigated through regular coordination meetings. Theoretically, this study contributes to the discourse on Islamic educational management by highlighting the integration of leadership and institutional strategy in one-roof pesantren systems. Practically, it provides insights for pesantren administrators seeking to strengthen institutional governance.